Image Processing in Road Traffic Analysis - Atkočiūnas, E.; Blake, R.; Juozapavičius, A.; Kazimianec, M. (Nonlinear Analysis: Modelling and Control, 2005)
The article presents an application of computer vision methods to traffic flow monitoring and road traffic analysis. The application is utilizing image-processing and pattern recognition methods designed and modified to the needs and constrains of road traffic analysis. These methods combined together gives functional capabilities of the system to monitor the road, to initiate automated vehicle tracking, to measure the speed, and to recognize number plates of a car. Software developed was applied in and approved with video monitoring system, based on standard CCTV cameras connected to wide area network computers.